CSF angiogenin levels in amyotrophic lateral Sclerosis-Frontotemporal dementia spectrum. Issue 1 (2nd January 2020) - Morelli, C.; Tiloca, C.; Colombrita, C.; Zambon, A.; Soranna, D.; Lafronza, A.; Solca, F.; Carelli, L.; Poletti, B.; Doretti, A.; Verde, F.; Maderna, L.; et al.
Abstract: Objective: Angiogenin (ANG) is a pro-angiogenic and neurotrophic factor with an important role in stress-induced injury, by promoting neovascularization and neuronal survival. Identification of loss-of-function mutations and evidence of beneficial effect of ANG administration in transgenic SOD1 G93A mice have linked ANG to the pathogenesis of Amyotrophic Lateral Sclerosis (ALS), stimulating interest in considering circulating ANG levels as an ALS disease biomarker although robust evidence is still lacking. Aim of our study was to assess differences of ANG levels in the cerebrospinal fluid (CSF) of a large cohort of patients with ALS and frontotemporal dementia (FTD) compared to controls and to explore correlations between ANG content and disease-related clinical variables. Methods: ANG levels were measured in CSF samples using a commercially available ELISA kit in 88 patients affected with ALS and/or FTD and 46 unrelated individuals (control group). Results: ANG levels didn't differ significantly between cases and controls. Patients with FTD or ALS-FTD showed significantly increased CSF concentration of ANG compared to ALS patients without dementia and controls in a multivariate regression model ( p < 0.001). No correlations were found in ALS/FTD patients between ANG levels and clinical parameters, including age, presence of C9orf72 repeat expansion, body mass index (BMI). Conclusions: our findings highlight a role of ANG as CSF biomarker useful to identify ALS patients with concurrent FTD and suggest that it should be further explored as potential biomarker for FTD.